Image analysis and recognition : 16th International Conference, ICIAR 2019, Waterloo, ON, Canada, August 27-29, 2019, Proceedings.: 16th International Conference, ICIAR 2019, Waterloo, ON, Canada, August 27-29, 2019, Proceedings. Part II (2019) - Unknown
No abstract available